A STUDY OF CODE MIXING IN ENGLISH NOVEL ENTITLED “CRAZY RICH ASIANS” BY KEVIN KWAN - Putri, Desi Eka; Djohan, Rita Sutjiati; Purwaningsih, Endang (Journal of Language and Literature, 2016)
The switching and the mixing code are now become a usual phenomenon in this globalization era. Code mixing can occur when the person understand the other language as well. The aims of the research are to find out the types of code mixing that frequently found in English novel entitled “Crazy Rich Asians” by Kevin Kwan, to find out the part of novel which is frequently used code mixing, and also to find out the reasons that make them do code mixing within a sentence in English novel entitled “Crazy Rich Asians” by Kevin Kwan. The writer uses the qualitative research method in analyzing and interpreting the data. The population in this research is the part one, part two, and part three of the novel. In addition, the sampling is the writer using the multi-stage cluster sampling in which the writer will choose the data randomly according to the types of the code mixing. The result of the research is there are 20% of alternation, 76% of insertion, and 4% of congruent lexicalization. Therefore, the most dominant types of the code mixing that found in the novel is insertion. The next is the percentage of the part of the novel in using code mixing are 55% for part one, 41% for part two, and 4% for part three. Thus, the part of the novel that dominant in using code mixing is the part one. This also makes the point for the reason in using code mixing. There are some reasons of using code mixing in the English novel entitled “Crazy Rich Asians” by Kevin Kwan are to express the attitude, the messages, the situations, and the emotions in order to make the story more expressive and be an original story. Another one is for talking about particular topic and also expressing group identity.Keywords: Sociolinguistics, Code Mixing, Types of Code Mixing, Alternation, Insertion, Congruent Lexicalization, The Reason of Using Code Mixing.